Separating environmental efficiency into production and abatement efficiency: A nonparametric model with application to U.S. power plants - Benjamin Hampf (Technische Universität Darmstadt, Department of Law and Economics, 2011)
In this paper we present a new approach to evaluate the environmental efficiency of decision making units. We propose a model that describes a two-stage process consisting of a production and an end-of-pipe abatement stage with the environmental efficiency being determined by the efficiency of both stages. Taking the dependencies between the two stages into account, we show how nonparametric methods can be used to measure environmental efficiency and to decompose it into production and abatement efficiency. For an empirical illustration we apply our model to an analysis of U.S. power plants.
Keywords: C14; L94; Q53; 330; nonparametric efficiency analysis; pollution abatement; network DEA; materials balance condition; fosil-fueled power plants; Ökoeffizienz; Produktion; Luftreinhaltung; Technische Effizienz; Stoffstrommanagement; Data-Envelopment-Analyse; Nichtparametrisches Verfahren; Theorie; Schätzung; Kraftwerk; USA